Distribution of profiles in relation to solitonic width for graphene nanolayer in high power regime - Orna T., D. André (2021)
The propagation of bright solitons in a high power regime in a graphene sheet is studied, where the alteration of the fraction of flowing energy within the sheet causes the variation in the propagating solitonic peaks, which when compared in relative unit allows confirm that the latter only depend on the length of the soliton. Finally the relation is proposed $\kappa=\rho_{i}/\rho_{j}$ showing the magnitude between solitons i j close or approaching to 2 µm and an application to characterize width of films with non-linear susceptibility.